2014
DOI: 10.1093/brain/awu169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic diversity of SMN1-negative proximal spinal muscular atrophies

Abstract: Peeters et al. review current knowledge regarding the phenotypes, causative genes, and disease mechanisms associated with proximal SMN1-negative spinal muscular atrophies (SMA). They describe the molecular and cellular functions enriched among causative genes, and discuss the challenges facing the post-genomics era of SMA research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 164 publications
(230 reference statements)
1
68
0
3
Order By: Relevance
“…Finally, due to distal greater than proximal weakness and initial presentation of respiratory distress, our patients fit a diagnosis of SMARD1. We highlight the dilemma of diagnosis for our patients that the clinically defined boundaries between these syndromes are not as impermeable as previously thought, consistent with recent literature (Darras, ; Peeters, Chamova, & Jordanova, ). As we transition from diagnoses hinged purely on clinical features to those based on underlying genomic alterations, these classifications will likely become further refined.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, due to distal greater than proximal weakness and initial presentation of respiratory distress, our patients fit a diagnosis of SMARD1. We highlight the dilemma of diagnosis for our patients that the clinically defined boundaries between these syndromes are not as impermeable as previously thought, consistent with recent literature (Darras, ; Peeters, Chamova, & Jordanova, ). As we transition from diagnoses hinged purely on clinical features to those based on underlying genomic alterations, these classifications will likely become further refined.…”
Section: Discussionsupporting
confidence: 89%
“…The clinical and genetic overlap with SMA and other neuromuscular disorders is significant. 9,10 The same gene may cause various phenotypes, and conversely 1 phenotype can be caused by >1 gene. For example, mutations in GARS are known to cause CMT type 2D (OMIM #601472) and distal SMA type V (dSMAV, OMIM #600794).…”
Section: Discussionmentioning
confidence: 99%
“…Electromyography (EMG) and muscle biopsy display chronic and active neurogenic findings. 9 Despite the growing number of genes implicated in SMA, no unifying molecular disease mechanism has been identified. 2 By genome-wide linkage analysis, SMAJ was linked to locus 22q11.2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Mutations in TUBB4A have been associated with a continuum of neurological conditions, ranging from early-onset severe hypomyelination with atrophy of the basal ganglia and cerebellum syndrome to the clinically milder, adultonset dystonia type 4. 1,[3][4][5][6][7][8] In general, the complexity of genotype-phenotype correlations is becoming increasingly evident with the use of new genetic technologies, which have repeatedly demonstrated that mutations in the same gene can cause widely different phenotypes, 9 whereas identical phenotypes can be caused by diverse gene defects. 6 The major challenge is to subsequently determine the underlying molecular mechanisms giving rise to this phenomenon.…”
Section: Reply: Mutations In Tubb4a and Spastic Paraplegiamentioning
confidence: 99%